PENGEMBANGAN FUNGSI KELEMBAGAAN DALAM PENYELENGGARAAN PEMERINTAHAN DI DESA CIKERUH, KECAMATAN JATINANGOR, KABUPATEN SUMEDANG - Setiawan, Irfan (Jurnal Ilmu Pemerintahan Widya Praja, 2025)
Village institutions are not only administrative entities, but also agents of change capable of bridging community interests and government policies. Based on this, this research examines the development of village institutional functions in supporting government administration in Cikeruh Village, Jatinangor District, Sumedang Regency. The research uses qualitative methods to emphasize problems regarding what they are according to phenomena in the field which originate from data, words or writings from individuals or behavior observed with informants from village officials, village institutions and the community. The research results show that developing the institutional capacity of Cikeruh Village requires strengthening village administration, increasing community participation, and optimizing resource management to achieve effective and efficient governance. Through active participation in Musrenbang and various empowerment programs, the community not only gets better infrastructure but also strengthens economic capacity, improves the quality of life, and builds strong togetherness. To optimize the development of institutional capacity in Cikeruh Village, it is recommended that the village government increase investment in training village officials, utilize information technology for more efficient administration, and strengthen coordination and communication between institutions. Community participation must continue to be encouraged through empowerment programs and Musrenbang, with the aim of building togetherness and improving the quality of life.